Factors of Committing Academic Dishonesty among Students in a Malaysian Public University - Hanisah, Kasbon; Siti Zurainiwati, Abdul Kadir (Globeedu Group, 2017)
Academic dishonesty among higher education students is a well-known issue and the phenomenon has caused hot debate in most part of the world. Even though the act of dishonesty is governed by the university regulations, but there are students who still commit to it (Caruana, Ramaseshan, & Ewing, 2000). This study therefore was conducted to identify the most influencing factors for committing academic dishonesty among the students in a Malaysian public university. The respondents of the study consisted of 289 students. The students were self-reported on the reasons for committing such acts of dishonesty. The students mostly reported that they committed academic dishonest to help their friends (235 or 81.9%); followed by the assessment was too difficult with 228 responds or 79.4% and the assessment was too time-consuming (222 or 77.1%). As such, the results illustrated that low prevalence rate of academic dishonest should be tackled at university level by looking at the seriousness of the matter and convey the messages to the students deliberately.